Implementation of Prophetic Education in Primary Education Institutions - Makherus Sholeh (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2018)
Educational institutions are part of the social institutions that exist in society. It is a space between other social institutions that interact with each other, influencing, both reciprocal influences, unidirectional influences, and the influence of mutualist symbiosis. The mutual influence of institutions can actually be controlled by actors so that they can be optimized to accelerate the achievement of institutional goals. The social institutions in question in the view of the author can be categorized into two types, namely; macrocosmic and microcosmic. Prophetic from the word prophetic which means prophethood or concerning the prophet. The English word comes from the Greek "prophetes" a noun to refer to the person who speaks early or the person who proclaims himself and means the person who speaks the future. Prophecy here refers to two missions, namely someone who receives revelation, is given a new religion, and is ordered to preach to his people called apostles (messengers), while someone who receives revelations based on existing religion and is not ordered to preach is called a prophet. Prophetic implementation in primary education institutions can be carried out through: (1) structural approaches, (2) formal approaches, (3) mechanical approaches, (4) organic approaches, while School Prophetic Education Development Strategies are 1) development at the level of values , 2) Development at the level of spirit and values, 3) Development at the technical level. 4) Development at the social level.